The Preparedness of the Faculty Members of Iran University of Medical Sciences for the Training of International Students - H Peyrovi; T Najafi Ghezeljeh (Iran University of Medical Sciences, 2020)
Background & Aims: An inherent element of the internationalization process of medical education is the assessment of preparedness to enter the international education market. The data obtained from such assessments could lay the basis for determining the policies and orientation of university planning. The present study aimed to determine the preparedness of the faculty members of Iran University of Medical Sciences for the training of international students. Materials & Methods: This descriptive, cross-sectional study was conducted at nine faculties and 88 departments of Iran University of Medical Sciences in Tehran, Iran during 2018-2019. In total, 900 questionnaires were distributed, and 378 faculty members completed the questionnaires. Data were collected in a self-report manner using a researcher-made questionnaire regarding the attitude and empowerment of lecturers in the training of international students. Electronic questionnaires were sent to the faculty members five times via email. Data analysis was performed in SPSS version 16 using the analysis of variance, Scheffe test, independent t-test, Fisher's exact test, and Chi-square. Results: The mean scores of the attitude and empowerment of the studied units regarding the training of international students were 53.14 ± 8.65 and 23.32 ± 5.17, respectively, which were considered relatively favorable. In addition, 61.4% of the studied units were not willing to cooperate in the training of international students. The main causes of willingness to partake in international training were classified as individual, professional, educational department, academic, and national categories. In addition, the causes of unwillingness were classified as individual and academic categories. Conclusion: According to the results, it is essential to provide the necessary infrastructures for university internationalization, as well as programs by the university authorities to improve the attitude and ability of faculty members to collaborate in international student training.